2019
DOI: 10.3390/catal9030297
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia-Supported Silver Nanoparticles for the Catalytic Combustion of Pollutants Originating from Mobile Sources

Abstract: This work presents the physicochemical characterization and activity of zirconia-supported silver catalysts for the oxidation of pollutants present in diesel engine exhaust (propane, propene, naphthalene and soot). A series of silver-supported catalysts AgxZ (x = 1, 5 and 10 wt.%, Z = zirconia) were prepared, which were studied by various characterization techniques. The results show that silver is mainly found under the form of small metal nanoparticles (<10 nm) dispersed over the support. The metallic pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
(112 reference statements)
0
11
0
1
Order By: Relevance
“…The temperature of the catalytic bed was monitored by a k-type thermocouple and the temperature was varied from 150 • C to 600 • C at 1.6 • C/min. A schematic diagram of the reaction systems has been reported in a previous work [44].…”
Section: Catalytic Activitymentioning
confidence: 99%
“…The temperature of the catalytic bed was monitored by a k-type thermocouple and the temperature was varied from 150 • C to 600 • C at 1.6 • C/min. A schematic diagram of the reaction systems has been reported in a previous work [44].…”
Section: Catalytic Activitymentioning
confidence: 99%
“…The separation of products was performed with an Alltech CTRI concentric column. A schematic diagram of the reaction system was reported in a previous work [24]. Propane conversion was calculated using the expression:…”
Section: Propane Oxidationmentioning
confidence: 99%
“…Previous studies carried out by our research group showed that tetragonal phases can be generated by adding various cations of interest in catalysis (Co(II), Cu(II), Ni(II), or Ag(I)) to a zirconia hydrogel. In addition, the effect of the addition of cations and their oxides on the redox capacity of catalysts for hydrocarbon oxidation reactions was shown [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen- and sulfur-based heterocyclic compounds show a wide variety of biological activity as antitumor, antibacterial, antifungal, and antiviral agents [ 23 ]. The preparation of several biologically active benzimidazole and benzotriazole derivatives has been described in previous reports [ 24 ]. Recently, Salauddin et al reported a review on benzimidazoles, biologically active compounds, which were discussed in terms of antimicrobial, antiviral, anticancer, antiprotozoal, anti-inflammatory, and analgesic activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%